are you saying for one you are trying to prove that cot theta = 1/tan theta? if so (imma change theta to x so it doesnt become a mess of words)
cotx becomes cos x/ sin x
so you have (cosx/sinx)= 1/tan x
mutiply both side by tan x giving you
(tanx) times (cosx/sinx)=1
tan x becomes sinx/cosx which will cancel out giving you 1=1
1)Use the definitions sin0(theta) = y/r, cos0(theta) = x/r and/or tan0(theta) = y/x to prove that
cot0(theta) = 1/tan0(theta)
2)For all 0(theta) prove:
a)cos(t) = 1/sec0(theta)
b. sec(t) = 1/cos0(theta)
1 answer